PEMANFAATAN TIK BERUPA APLIKASI ONLINE DALAM PEMBELAJARAN PASCA PANDEMI DI SEKOLAH DASAR - Rudi Prasetyo; Henry Praherdhiono; Candra Utama (LPPM Institut Pendidikan Nusantara Global, 2022)
The ability to master ICT is one of the efforts to increase teacher professionalism in carrying out learning. The purpose of this research is to describe online applications that teachers use for learning after the Covid19 pandemic. This research is a survey research. The subject of this study involved a sample of teachers in Blitar City, totaling 54 people consisting of 13 men and 41 women with an age range of 26 years to 59 years. The teachers involved in this research teach in both public and private schools in the city of Blitar. The teachers involved in this study had more than five years of teaching experience. Data collection was carried out using a survey questionnaire by filling out the Google form. Data analysis was carried out simultaneously and integrated descriptively. The results of this study indicate that the 5 online applications most frequently used by teachers in learning are Whatsapp, Google Forms, Google Meet, Zoom Meeting, and Quizizz.